Clinical Scoring of Positive Histophatology Findings for Inflammatory Bowel Disease at Four Hospital in Jakarta - Dasril Nizam; Marcellus Simadibrata; Chudahman Manan; Dadang Makmun; Murdani Abdullah; Adang Bachtiar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Background: Inflammatory bowel disease (IBD) in the form of Crohn’s disease (CD) or ulcerative colitis (UC) is chronic IBD which still difficult to diagnose and clinically characterized by exacerbation and spontaneous remission. A precise diagnosis is needed and essential for appropriate treatment. Most of internists in Indonesia have to cope with a condition of poorly equipped endoscopic facilities - especially colonoscopy and subsequently refer their patients to endoscopic centers with colonoscopy facilities as well as sending biopsy specimens for histopathology examination. They also should be concerned that it would be expensive, time- consuming, and patients may suffer from considerable distress while waiting for the results of diagnostic confirmation. Therefore, we were interested in studying the clinical scoring for IBD to determine the diagnosis of possible IBD by assessing the combination of clinical reporting aspects, identification of probable IBD and histopathology examination Method: The study design was cross-sectional. We collected data pertinent to this study from medical records of patients with IBD clinical features at the endoscopic units of four hospitals in Jakarta between 1999 and 2009. Student t-test and logistic regression analysis were used for the statistic examination. Results: Based on colonoscopy examination, there were 213 patients with positive IBD and 173 patients with negative results. Histopathology results were considered as the gold standard in diagnosis of IBD. The mean clinical score was 9 (nine) points. Subjects with positive histopathology findings were significantly had higher average score than those with negative histopathology findings. Using ROC curves, we found cut-off score of 10 points with a sensitivity and specificity of 73% and 88% consecutively; while by applying logistic regression analysis, we found odds ratio (OR) of 20 (9.9-40.0 Conclusion: The clinical scoring for IBD is a valuable diagnostic tool in determining definitive diagnostic of IBD based on histopathology findings Keywords: clinical scoring, histopathology findings, definitive IBD